Analisis Frekuensi Interaksi Mahasiswa Akutansi Syariah Angkatan 2023 terhadap Efektivitas Pembelajaran Online (Jurnal Kendali Akuntansi, 2025)
This study aims to examine the effect of interaction frequency among 2023 cohort Sharia Accounting students on the effectiveness of online learning. The research was motivated by the increasing implementation of online classes, especially during lecturer absences or national holidays. A quantitative approach was applied through a questionnaire distributed to students. Data were analyzed using validity, reliability, normality, homogeneity, and One Way ANOVA tests. The results indicate that although students showed a reasonable frequency of interaction, there was no significant effect on learning effectiveness. This suggests that interaction alone may not be the key factor in successful online learning. Other elements such as motivation, teaching methods, and learning environment may also play an important role. The study recommends that students engage more consistently in class and that lecturers develop more engaging and interactive online learning strategies.